Does Robin Hood Use a Lightsaber?: Automated Planning for Storytelling - Simon, Nisha (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
Humans have been using stories to entertain, educate, and persuade audiences for centuries. The advent of modern AI tools in the form of Large Language Models (LLMs) such as chatGPT continues to fulfill this purpose. However while recent work has shown that LLMs can successfully be used for narrative generation, they lack coherence and can be prone to repetition and stilted language. Automated Planning can therefore be combined with Natural Language text generation to create narratives (stories) that are logical, coherent, and believable. A planning model provides scaffolding to an LLM so that the LLM’s language generation is context-dependent, in order to allow users to create more coherent, logical, and believable stories in a variety of domains.